A streamlined multidisciplinary metabolic clinic in psychiatric recovery service: a pilot study - Leung, Kelvin CY.; Bakr, Bianca; Chung, Cindy; Parmar, Mayuri; Elhindi, James; Brakoulias, Vlasios (Frontiers in Psychiatry, 2024)
Background The metabolic syndrome (MetS) is a collection of risk factors for cardiovascular disease and type-2 diabetes, that includes central obesity, hypertension, hyperglycaemia and dyslipidaemia. An audit indicated inadequate MetS screening in an Australian psychiatric recovery service. Objectives We aimed to improve MetS screening, identification and intervention by offering streamlined lifestyle education, clinical reviews and discharge planning. This pilot program prioritized holistic, culturally-sensitive, patient-centric, and trauma-informed approaches to enhance metabolic health outcomes. Methods A Metabolic Clinic was piloted in two psychiatric rehabilitation cottages (n=35), which involved disciplines of dietetics, exercise physiology, diversional therapy, occupational therapy, peer workforce, social work, clinical psychology, pharmacy, nursing and medical. Another cottage (n=15) was assigned as the comparison and received standard care. A 12-week, 3-times-per-week lifestyle and behavioral program, called MetFit, was devised and offered to those identified at screening for the treatment cottages. Outcome measures were feasibility measures, the five metabolic parameters (waist circumference, blood pressure, fasting serum triglycerides, high-density lipoprotein, and glucose), functional measures, and a meal questionnaire. Results The treatment cottages had qualitative advantages in screening and identifying MetS. Of four enrolled consumers in MetFit, an improvement of triglycerides (p=0.08), squats (p=0.02), and push-ups (p=0.07) was observed. Major challenges of enrolment included an overall lack of acknowledgment of its importance, poor motivation of consumers and resources limitation. Conclusions The one-stop provision of groups, peer support and inpatient pathway with multidisciplinary team-integration was generally accepted by consumers and the MDT and has iteratively demonstrated the urgent need for consumer-centered physical care and a cultural shift to foster collaboration within a psychiatric service.